Building a Literature Culture in Islamic Education Units: Concept and Strategy - Saefrudin Saefrudin (Journal of Advanced Multidisciplinary Research, 2021)
In the 21st century, the ability of literate learners closely related to the demands of reading skills that lead to the ability to understand information in an analytical, critical, and reflective. Based on the current reality in most educational institutions in Indonesia, especially in the institutions of Islamic formal education encountered problems related to the acculturation of literacy in schools. The problems include low interest in reading, reading motivation among learners, and demands the ability to read in the sense of understanding the text analytical, critical, and reflective. Thus, several attempts were made to develop a culture of reading is to: a) Allowing learners to read at least 15 minutes before the learning activity begins; b) Setting up a library or reading room comfortable and enjoyable at school; c) Absolutely the proper functioning of the library as a means of learning resources; d) Enhancing the reading material with the procurement of varied and interesting books in the school; e) create symbols that can enhance the enthusiasm of the spirit of reading; and f) Hold a book review contest among students / classes regularly at school. Of course, for students who win should be given an appreciation / reward.